BELOW TAKEOVER EFFICIENCY OF VOLLEYBALL PLAYERS - VIRGIL LARIONESCU (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
The aim of the present research is to provide a comparative analysis regarding the takeover of service and taking the attack, leading to precise knowledge and fair game in these situations actually of great importance in achieving training important, appropriate and accordance with the current requirements of sports performance.